2017
DOI: 10.26502/jppd.2572-519x0025
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Brain-Derived Neurotrophic Factor in the Pathophysiology of Psychiatric and Neurological Disorders

Abstract: Brain-derived neurotrophic factor (BDNF) is a neurotrophin highly expressed in the brain with a potent influence on several aspects of neuronal function. Since its discovery in the early 1980s, BDNF has prompted a great interest in better understanding its physiological role and has been established as the main central neurotrophic factor. BDNF is initially synthesized as a precursor, pro-BDNF, which is then cleaved to form mature BDNF (m-BDNF). A regulated balance between pro-BDNF and m-BDNF is crucial for ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 61 publications
(119 reference statements)
0
15
0
Order By: Relevance
“…Therefore, it is also important to point out the limitations of this study. Besides a single blood sample per volunteer, we only measured total BDNF levels instead of pro- and mature BDNF molecules, which are more specific biomarkers of apoptosis and neuroplasticity, respectively (Angoa-Perez et al, 2017). With respect to the sample, it was limited to a modest number of patients with treatment-resistant depression and comorbid personality and anxiety disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is also important to point out the limitations of this study. Besides a single blood sample per volunteer, we only measured total BDNF levels instead of pro- and mature BDNF molecules, which are more specific biomarkers of apoptosis and neuroplasticity, respectively (Angoa-Perez et al, 2017). With respect to the sample, it was limited to a modest number of patients with treatment-resistant depression and comorbid personality and anxiety disorder.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports show lower BDNF levels in brains with neurological diseases [ 2 4 , 10 , 11 ]. Non-invasive near-infrared in vivo BLI using Bdnf-Luc mice and TokeOni will allow changes in Bdnf expression in the brain under physiological and pathophysiological conditions to be examined.…”
Section: Discussionmentioning
confidence: 99%
“…Brain-derived neurotrophic factor (BDNF), a member of the neurotrophin family, is fundamentally involved in a variety of functions in the developing and mature brain [ 1 ]. Consistent with the crucial roles of BDNF in the central nervous system (CNS), alterations in BDNF levels have been found in the brains of patients with neurodegenerative or neuropsychiatric diseases [ 2 4 ]. Abnormal expression levels of BDNF have been reported in the postmortem brains of Alzheimer’s disease [ 5 ], Parkinson’s disease [ 6 ], Huntington’s disease [ 7 ], depression [ 8 ], and schizophrenia [ 9 ].…”
Section: Introductionmentioning
confidence: 89%
“…Both human and animal studies have shown that maternal iron deficiency affects the fetal production of BDNF and hippocampal morphogenesis [ 10 , 11 ]. Moreover, in many neurological and psychiatric diseases, such as Parkinson’s disease, Huntington’s disease, schizophrenia, Alzheimer’s disease, and depression, the concentration of BDNF was found to be low [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%